2023
DOI: 10.3389/fped.2023.1164473
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pulmonary hypertension severity in the first 48 h in neonates with prenatally diagnosed congenital diaphragmatic hernia

Abstract: IntroductionPulmonary hypertension (PH) is one of the major contributing factors to the high morbidity and mortality in neonates with congenital diaphragmatic hernia (CDH). The severity and duration of postnatal PH are an established risk factor for patient outcome; however, the early postnatal dynamics of PH have not been investigated. This study aims to describe the early course of PH in CDH infants, and its relation to established prognostic markers and outcome measures.MethodsWe performed a monocentric ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Approximately 85% of CDH newborns manifest pulmonary hypertension within the first 48 h of life, with limited treatment options currently available (23,24). Additionally, Leyens et al reported the dynamics of PH in the first 48 h of life at three defined times point of echocardiography and observed a fluctuation in PH severity in approximately two third of all patients (25). We had similar results with those reports, while we not only examined every patient and had a primary diagnosis for the first several hours after birth, but measured changes of PH after medical treatment on the second day or before the surgery within 24 h. On the second echo, the PDA directionality of shunting and diameter changed, which predicted outcomes in this patient population from our results.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 85% of CDH newborns manifest pulmonary hypertension within the first 48 h of life, with limited treatment options currently available (23,24). Additionally, Leyens et al reported the dynamics of PH in the first 48 h of life at three defined times point of echocardiography and observed a fluctuation in PH severity in approximately two third of all patients (25). We had similar results with those reports, while we not only examined every patient and had a primary diagnosis for the first several hours after birth, but measured changes of PH after medical treatment on the second day or before the surgery within 24 h. On the second echo, the PDA directionality of shunting and diameter changed, which predicted outcomes in this patient population from our results.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of PH was graded as mild PH (pulmonary arterial pressure [PAP] < ⅔ systemic systolic pressure), moderate PH (⅔ of systemic pressure to systemic pressure), or severe PH (suprasystemic pressure) as previously described 15 . This assessment includes: (a) ductus arteriosus flow pattern, (b) position of the intraventricular septum, and (c) velocity of the tricuspid regurgitation jet if present.…”
Section: Methodsmentioning
confidence: 99%